Fraud Reporting Portal Is Easy And Useful? - Hermawan, Aditya Pradina; Hapsari, Aprina Nugrahesthy Sulistya (Gorontalo Accounting Journal, 2021)
The case of fraud is currently a hot topic, according to ACFE in 2018 the rate of fraud in the education sector in the Asia-Pacific region is reached five percent. There are several ways to detect fraud in order to overcome or minimize the occurrence of fraud, one of which is whistleblowing. Based on the ACFE survey in 2020, shows that currently, the form of fraud reporting media tends to be online or electronic. This research aims to explore the ease of use, usefulness, and importance of fraud reporting information systems in educational institutions using the TAM theory. This research method is descriptive qualitative. The results showed that the number of reports submitted to the fraud reporting portal was not driven by the ease and usefulness of the reporting portal service. The results of this study, apart from being able to add insight and literature, can also be used as material for consideration in making improvements related to the use of fraud reporting information systems, especially in educational institutions.